2017
DOI: 10.1152/ajpendo.00096.2017
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of UCP1 enhances ex vivo aortic vasomotor function in female but not male mice despite similar susceptibility to metabolic dysfunction

Abstract: Females are typically more insulin sensitive than males, which may be partly attributed to greater brown adipose tissue (BAT) activity and uncoupling protein 1 (UCP1) content. Accordingly, we tested the hypothesis that UCP1 deletion would abolish sex differences in insulin sensitivity and that whitening of thoracic periaortic BAT caused by UCP1 loss would be accompanied with impaired thoracic aortic function. Furthermore, because UCP1 exerts antioxidant effects, we examined whether UCP1 deficiency-induced meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 69 publications
1
15
1
Order By: Relevance
“…However, it is important to note that not all studies have supported that there is a sex difference in BAT content and/or activity (van der Lans et al 2013). In fact, when we compared BAT UCP1 levels in male and female mice (housed under the same temperature conditions as the present study), we did not find an increase in UCP1 protein content (Winn et al 2017a), although we did find greater UCP1 gene expression in females. Others have had similar findings in mice where no sex differences in BAT UCP1 content were found (Grefhorst et al 2015).…”
Section: Introductioncontrasting
confidence: 52%
See 2 more Smart Citations
“…However, it is important to note that not all studies have supported that there is a sex difference in BAT content and/or activity (van der Lans et al 2013). In fact, when we compared BAT UCP1 levels in male and female mice (housed under the same temperature conditions as the present study), we did not find an increase in UCP1 protein content (Winn et al 2017a), although we did find greater UCP1 gene expression in females. Others have had similar findings in mice where no sex differences in BAT UCP1 content were found (Grefhorst et al 2015).…”
Section: Introductioncontrasting
confidence: 52%
“…All mice were fed a standard chow diet (3.3 kcal/g of food, 13% kcal fat, 57% kcal carbohydrate and 30% kcal protein, 5001, LabDiet, St. Louis, MO, USA) and were housed two to three per cage (within group) in a light cycle from 07:00 to 19:00 h at 25°C. In previous studies, these conditions were shown to be adequate in preventing thermostress (Winn et al 2017a). WT and UCP1KO female mice underwent OVX or sham (SHM) operations at 12 weeks of age creating four distinct groups (n = 10/group): (1) WT SHM, (2) WT OVX, (3) KO SHM and (4) KO OVX.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats, females have significantly higher UCP1 abundance in BAT than males, though these sex-associated divergences disappear or reverse during cold- and diet-induced thermogenesis [22], [24], [25]. Despite higher Ucp1 mRNA levels in interscapular BAT (iBAT) of female mice [26], there are no significant sex differences in UCP1 protein levels in iBAT or inguinal WAT (iWAT) [26], [27]. Regarding these conflicting data, sexual dimorphism in Ucp1 gene expression and thermogenic capacity and activity of brown and brite fat in different anatomical regions requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, comparisons are made within the artery, limiting the inherent between-artery and between-animal variability. Aortic rings were mounted in wire myograph organ bath chambers (620 M, Danish Myo Technology, Hinnerup, Denmark) containing warmed physiological saline solution gassed with 95% O 2 -5% CO 2 and maintained at 37 C as previously described (43,44). Aortic rings were treated with 80 mM KCl to ensure viability.…”
Section: Experimental Protocol 3 In Isolated Mouse Arteries: Insulin-induced Suppression Of Catecholamine-induced Vasoconstriction and Romentioning
confidence: 99%